Perancangan Arsitektur Sistem Informasi Kotak Saran Pada PT. Varta: Information System Architecture Design Suggestion Box At PT. Varta - Ghea Paulina Suri (YCMM, 2022)
The success of this program in the process is influenced by several factors, such as the comfort of employees, the company, and industrial facilities. And the factors that support the success of the design of the information system architecture of PT. Varta's suggestion box are comfort and opinions and criticisms from the employees of the company so that they achieve comfort in work. And the purpose of this program is to become a forum for suggestions for employees to achieve a level of effectiveness in working and managing data, and this application is one of the upgrade processes from a manual system to an online system where the manual system is very old school not yet effective in the industrial era 4.0, therefore the design Suggestion box information system architecture is very effective in this day and age, because it no longer requires paper and pen to convey suggestions, and one application that can be concluded to solve a problem so that the company and employees can improve performance and can obtain good performance results. effective.